Supercontinuum from Zr-EDF using Zr-EDF mode-locked fiber laser - Ahmad, Harith; Awang, Noor Azura; Zulkifli, Mohd Zamani; Thambiratnam, Kavintheran; Paul, M. C.; Das, S.; Harun, Sulaiman Wadi (Institute of Physics Publishing, 2012)
We propose and demonstrate the generation of a supercontinuum (SC) spectrum from a 10 m long silica fiber co-doped with zirconia-yttria-alumino and erbium (Zr-EDF) as a non-linear medium. The proposed system utilizes a 2 m long Zr-EDF in a ring laser configuration to generate mode-locked pulses at 1560 nm based on the non-polarization rotation (NPR) technique. The fiber laser generates a mode-locking spectrum from 1526 to 1640 nm with a peak power of –10 dBm at approximately 1565 nm as well as a 6.1 nm bandwidth at the 3 dB level. The generated mode-locked pulses have average and peak powers of 15 mW and 1 kW respectively with a repetition rate of 23.2 MHz. These pulses are subsequently used to generate the SC spectrum from the 10 m Zr-EDF, with the SC spectrum obtained having a 200 nm bandwidth from 1500 nm as well as a large 3-dB bandwidth of 68.2 nm. The SC pulse width is 0.59 ps with a symmetrical shape at about 1600 nm and a 3-dB bandwidth of approximately 0.12 ps. This is the first report of a zirconia host employed as a non-linear medium for SC generation.